STUDI PENGARUH DARING LEARNING TERHADAP MINAT DAN HASIL BELAJAR MATEMATIKA MAHASISWA PGSD ERA PANDEMI COVID-19 - Wulan Sutriyani (Tunas Nusantara, 2020)
Utilization of information technology has a very important role in the implementation of distance learning in the midst of a co-pandemic19. This study aims to examine the effect of online learning on the interests and learning outcomes of college students in the pandemic covid19. The method used in this study was quantitative conducted in the Unisnu semester 4 PGSD FTIK Study Program with a sample of 72 students. Methods of data collection using questionnaires, tests, and documentation. know the interests of students regarding online learning based learning in elementary mathematics learning courses. tests are used to obtain student learning outcomes using online learning. The findings of this study indicate that students' interest in learning in elementary mathematics learning courses based on online learning using the WA Group and E learning platforms is included in the agreed category which means online learning has a positive influence on student learning interest. Student learning outcomes in elementary mathematics learning courses conducted by paired sample t-test and obtained Sig. (2-tailed) of 0,000 <0.05, then Ho is rejected, Ha is accepted so that it can be concluded that the use of online learning in elementary mathematics learning courses has a positive effect on student learning outcomes at PGSD FTIK Unisnu Jepara.Keywords: Daring Learning, Interest to learn, Learning outcomes